2017
DOI: 10.1126/science.aal3908
|View full text |Cite
|
Sign up to set email alerts
|

A switch from canonical to noncanonical autophagy shapes B cell responses

Abstract: Autophagy is important in a variety of cellular and pathophysiological situations; however, its role in immune responses remains elusive. Here, we show that among B cells, germinal center (GC) cells exhibited the highest rate of autophagy during viral infection. In contrast to mechanistic target of rapamycin complex 1-dependent canonical autophagy, GC B cell autophagy occurred predominantly through a noncanonical pathway. B cell stimulation was sufficient to down-regulate canonical autophagy transiently while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
94
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(107 citation statements)
references
References 29 publications
9
94
4
Order By: Relevance
“…CQ was recently shown to induce LC3 conjugation onto endosomal membranes [49] and subsequently this event was attributed to the induction of a non-canonical form of autophagy upon short-term treatment. This non-canonical form of autophagy does not involve ATG13, ATG9A and PIK3C3/ VPS34 [29,87]. We also found that CQ indeed stimulates a mild autophagic sequestration response for a short period, which is in line with early studies that showed a peak in autophagic vesicle appearance within the first 3 h of exposure to CQ [9,64,67].…”
Section: Discussionsupporting
confidence: 91%
“…CQ was recently shown to induce LC3 conjugation onto endosomal membranes [49] and subsequently this event was attributed to the induction of a non-canonical form of autophagy upon short-term treatment. This non-canonical form of autophagy does not involve ATG13, ATG9A and PIK3C3/ VPS34 [29,87]. We also found that CQ indeed stimulates a mild autophagic sequestration response for a short period, which is in line with early studies that showed a peak in autophagic vesicle appearance within the first 3 h of exposure to CQ [9,64,67].…”
Section: Discussionsupporting
confidence: 91%
“…G9A inhibitors have been reported to induce autophagy, this was also observed in the B-cell response to this G9A inhibitor with rapid induction of features consistent with autophagy in ABCs following UNC0638 treatment (Supplemental Figure 11B and C). Autophagy can have a protective role in PC differentiation, 51, 52 and despite the stress response phenotypic differentiation showed limited differences with modest impairment in the downregulation of CD20 and the upregulation of CD38 (Supplemental Figure 11D). Furthermore, consistent with a delayed impact as would be anticipated with an epigenetic mechanism cell division was modestly impaired at day 4 (24h of treatment) and delayed by one generation at day 5 and 6 where the population mode for UNC0638 treated cells fell at generation 6 rather than 7 (Supplemental Figure 11E).…”
Section: Resultsmentioning
confidence: 99%
“…V-ATPase inhibitor bafilomycin A (BafA) blocks LC3II lysosomal degradation during canonical autophagy. Chloroquine (CQ) inhibits the fusion between the autophagosome and lysosome, thereby rendering it capable of revealing total autophagic flux, inclusive of both canonical and noncanonical autophagy (33,34). Thus, the difference between the effects of CQ versus BafA on LC3-II/I ratios is attributed to noncanonical autophagy.…”
Section: Wipi1 Regulates Map4 Expression Under Conditions Of Aldostermentioning
confidence: 99%